New species of salamander (Caudata: Plethodontidae: Cryptotriton) from Quebrada Cataguana, Francisco Morazán, Honduras, with comments on the taxonomic status of Cryptotriton wakei - Mccranie, James R.; Rovito, Sean M. (Zootaxa, 2014)
We describe a new species of the plethodontid salamander genus Cryptotriton from Honduras after comparing morphological, molecular, and osteological data from the holotype to that of the other nominal forms of the genus. The new species differs from all of the known species of Cryptotriton in at least one character from all three datasets. We also suggest placing C. wakei in the synonymy of C. nasalis after examining the morphological and osteological characters of the single known specimen of C. wakei.